The Level of Knowledge of Final Year Dental Students about the Etiology and Treatment Measures of Squamous Cell CarcinomaLesions - Mansour Sardarpour; Atousa Aminzadeh Gohari (Isfahan University of Medical Sciences, 2023)
Carcinogenesis of the oral cavity is a complex process and oral cancer is one of the 10 most common cancers worldwide. Oral squamous cell carcinoma accounts for 90% of oral cancers, the most important risk factors of Oral squamous cell carcinoma(OSCC) areusing tobacco and drinking alcohol. Early detection of cancerous and pre-cancerous lesions and timely referral is the most important factor in reducing mortality associated with OSCC, the purpose of this study is to investigate the level of knowledge of final year dental students at Isfahan Islamic Azad University (Khorasgan) during 1400-1401 regarding the etiology, Diagnosis and treatment of oral squamous cell carcinoma.Materials & Methods:The present study was carried out in a descriptive and analytical method and in a census method, and a researcher-made questionnaire was distributed among the students in person; Data analysis was done in two descriptive and inferential sections. The collected data were analyzed using the non-parametric Mann-Whitney test and the Spearman correlation coefficient at the error level of 0.05% (p value ≤0.05).Results:In this study, about 60.6% of students were in the 11th semester and about 39.4% were in the 12th semester with average age of 25.73 years. The average awareness score was approximately average (score 5.74 out of 10). There was no significant difference between the average knowledge of the 11th and 12th semester students regarding etiology, while 12th semester students showed significantly higher knowledgein terms of prognosis and treatment compared to 11th semester students.There was no significant difference in the average knowledge between students of different ages in the fields of etiology and treatment.Conclusion:The results of the present study showed that the level of knowledge and awareness among students regarding OSCC lesions is far from satisfactory